Silicon to mitigate stress due to manganese deficiency and water deficit in pre-sprouted sugarcane seedlings (Bibliographic Review) - Teixeira, Gelza Carliane Marques [UNESP]; Rocha, Antonio Márcio Souza [UNESP]; Oliveira, Kamilla Silva [UNESP]; Dos Santos Sarah, Marcilene Machado [UNESP]; De Oliveira Filho, Antonio Santana Batista [UNESP]; De Mello Prado, Renato [UNESP]; Palaretti, Luiz Fabiano [UNESP] (UNESP - Universidade Estadual Paulista, 2020)
A bibliographic review was carried out on the benefits of silicon (Si) in alleviating stress at the physiological and nutritional level in pre-sprouted sugarcane seedlings (PSS) submitted to stress due to nutritional deficiency and water deficit. It was evident that Si can be used to mitigate the damage caused by micronutrient deficiency, such as manganese (Mn), because it reduces the damage caused by stress and increases the accumulation of dry matter. And yet, that Si can potentiate fertilizations with Mn, increasing the response of plants even in the sufficiency of the micronutrient, because it acts in places similar to Mn in the metabolism of plants. It has also been shown that the supply of Si in the MPB formation phase or after transplantation via fertigation, provides beneficial effects that contribute to maintaining the water content in the leaf tissue and reducing the damage caused by water deficit, providing greater matter production. And this occurs, even when the seedlings are subjected to different intensities of water deficit, in the initial stage of development and in the regrowth of the knuckle, in different types of sugarcane (Saccharum officinarum L. and Saccharum spontaneum L.) drought tolerance and when grown in different soil types. In conclusion, the supply of Si in sugarcane MPB should be considered a new management strategy in production systems because it can increase the tolerance to various stresses and thus, increase the productivity of areas destined to the cultivation of sugarcane.
Keywords: Abiotic stress; Beneficial element; Nutritional disorder; Plant nutrition; Saccharum spp.; Water deficiency.